2016
DOI: 10.1007/978-3-319-49676-4_2
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of Manufacturing Buildings Through the Depreciated Replacement Cost Approach

Abstract: It is well-known that the persisting crisis of the real estate market, in the wake of the large-scale financial and economic crisis starting from the year 2008, is leading to diminishing property values. An earlier and more pronounced effect lies in the lower number of transactions resulting in the scarcity of sales that characterizes several sub-markets, including the one concerning the manufacturing buildings. Within the real-estate appraisal discipline, the aforementioned framework entails growing difficult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Regarding the use of the results of this paper within the research in progress on the subject, we should stress that at present there is a small number of studies on the DRC method [33][34][35][36][37][38][39][40][41]; the methodology presented here, is, thus, one of the first available operational variations of DRC, which is already held as one of the three methodologies currently provided by the real estate valuation discipline for the estimate of the MV of a property.…”
Section: Results: Analysis and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the use of the results of this paper within the research in progress on the subject, we should stress that at present there is a small number of studies on the DRC method [33][34][35][36][37][38][39][40][41]; the methodology presented here, is, thus, one of the first available operational variations of DRC, which is already held as one of the three methodologies currently provided by the real estate valuation discipline for the estimate of the MV of a property.…”
Section: Results: Analysis and Discussionmentioning
confidence: 99%
“…The analysis carried out on the application methodologies of DRC showed that there is strong potential for implementing this procedure in real estate evaluation [33][34][35][36][37][38] and in facility management [39][40][41][42][43]; in the first field, DRC may be used, as already argued, when comparables are missing and when other estimation procedures cannot be used. In facility management, DRC makes it possible to evaluate the convenience of a maintenance program, which is a function of the market value of the building, which, in turn, depends on factors that affect the urban rent [42].…”
Section: Valuation Methods Supporting the Management Of Public Property Assetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the methodological issues discussed in the previous sections, DRC is ever more widespread in the professional practice because of operational reasons, not least the lack of transaction data due to the real estate market recession (COPIELLO et al 2017). Since there are situations wherein making use of DRC is unavoidable, we aim to discuss several improvements to be brought to the method.…”
Section: Depreciated Replacement Cost Variantmentioning
confidence: 99%